A nationwide evaluation of spontaneous coronary artery dissection in pregnancy and the puerperium. Issue 24 (13th July 2016) - Faden, Majed S; Bottega, Natalie; Benjamin, Alice; Brown, Richard N
Abstract : Objective: Spontaneous coronary artery dissection (SCAD) is a rare and potentially lethal cause of myocardial infarction (MI). The purpose of our study was to estimate the prevalence and maternal outcomes of pregnancies complicated by SCAD. Materials and methods: A population-based cohort study on all births identified in the Healthcare Cost and Utilization Project from 2008 to 2012. Disease prevalence was calculated and logistic regression was used to estimate the adjusted odds ratio (aOR) for risk factors and different maternal complications. Results: A total of 4 363 343 pregnancy-related discharges were evaluated. 79 cases of SCAD were identified resulting in a prevalence of 1.81 per 100 000 pregnancies. The mean maternal age at the time of diagnosis was 33.4 years (±5.2). Chronic hypertension (aOR, 2.67; 95% CI 1.18 to 6.03), lipid profile abnormalities (aOR, 48.22; 95% CI 24.25 to 95.90), chronic depression (aOR, 3.56; 95% CI 1.43 to 8.83) and history of migraine (aOR, 3.93; 95% CI 1.52 to 10.17) were associated with an elevated risk for SCAD. MI was diagnosed in 66 (85.5%) cases of SCAD with anterior and subendocardial territories being the most common locations. Thirty one patients (40%) with SCAD underwent angioplasty with the majority receiving stents, which was associated with a longer hospital stay than those treated conservatively or with bypass. Conclusions: SCAD is a rare aetiology of MI; risk factors and outcomes are illustrated in the current study. The puerperium is an important period for the development of pregnancy-related SCAD. Careful evaluation of pregnant and postpartum women with chest pain is warranted, especially if these risk factors are identified.